Empowering Santri Through Entrepreneurship and Digital Skills Development at Asy-Syifa Al-Islami Islamic Boarding School - Ahmad Maulidizen; Kamran Azizli; Fauzan Ulwan Fadhlurrahman; Kamran Abdullayev (SocietalServe: Journal of Community Engagement and Services, 2026)
This community engagement program aimed to strengthen entrepreneurial capacity and digital literacy among santri at Asy-Syifa Al-Islami Islamic Boarding School, Parung Bogor, Indonesia. The program was designed in response to the growing importance of entrepreneurship and digital competencies in supporting youth empowerment, economic participation, and sustainable community development. The activities involved Islamic boarding school students who had limited access to entrepreneurship education, digital business training, and practical technology-based learning opportunities. To address these challenges, participatory workshops, mentoring sessions, collaborative discussions, and practical digital entrepreneurship training were implemented over a three-month period involving 55 participants. The program focused on entrepreneurial mindset development, digital marketing, financial literacy, social media utilization, and small business management skills. The findings demonstrated significant improvements in entrepreneurial awareness, digital literacy, communication skills, creativity, teamwork, and self-confidence among participants. Qualitative results also revealed increased motivation among santri to develop small businesses and utilize digital platforms productively. Participants showed greater readiness to engage in entrepreneurship activities and adapt to technological developments after completing the program. The integration of entrepreneurship education and digital skills training proved effective in promoting youth empowerment and sustainable community participation. Overall, the program highlights the importance of community-based entrepreneurship and digital literacy initiatives in strengthening the socio-economic capacity of Islamic boarding school students